IDEOLOGI MUHAMMADIYAH: KAJIAN FILOSOFIS KONSEP DASAR DAN PEMBENTUKAN KEPRIBADIAN KADER - Pohan, Selamat; Riswanda, Wahyu; Husnul Khotimah, Muti; Rozi Pasaribu, Fahrul; Zahara, Novita; Akbar, Jihan (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
This article aims to explain the concept of Muhammadiyah ideology philosophically and ideologically, analyzing its manifestation in the preamble to the articles of association and bylaws (AD/ART), seven philosophies, and the role of 17 groups of verses in the Qur'an in shaping the character of cadres. This study uses philosophical and ideological analysis methods with a literature review approach, referring to fundamental documents and thematic interpretations used by Muhammadiyah. The results of the study conclude that Muhammadiyah's ideology is a comprehensive system rooted in tawhid, emphasizing righteous deeds, ijtihad, knowledge, and morals for social transformation towards khairu ummah. These core principles are manifested in the seven main ideas of the preamble, operationalized by the AD/ART, deepened by the seven philosophies, and crystallized for self-development through 17 groups of verses from the Qur'an. This ideology guides Muslims towards a just, progressive society based on the values of tawhid.